«МИСТИКА» И «ДУХОВНЫЙ ОПЫТ», ИЛИ В ПРОСТРАНСТВЕ УСКОЛЬЗАЮЩИХ ГРАНИЦ - КОМПАНИЕЦ, ЛИЛИЯ ВИКТОРОВНА (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье проводится анализ смыслового поля термина «мистика», а также специфики его отношения к «духовному опыту». Проводится изучение проблемы демаркации между обозначенными понятиями. Устанавливается подвижность границ, их взаимное смысловое проникновение, дополнение. Мистика презентуется как универсальное комплексное явление культуры, атрибутом и источником которого выступает «духовный опыт». Даётся авторское определение термина «мистика». Компанієць Л.В. «МІСТИКА» І «ДУХОВНИЙ ДОСВІД», АБО У ПРОСТОРІ ЗНИКАЮЧИХ МЕЖ У статті проводиться аналіз смислового поля терміна «містика», а також специфіки його відношення до «духовного досвіду». Проводиться вивчення проблеми демаркації між зазначеними поняттями. Встановлюється рухливість меж, їх взаємне проникнення, доповнення. Містика презентується як універсальне комплексне явище культури, атрибутом і витоком якого виступає «духовний досвід». Дається авторське визначення терміна «містика». Ключові слова: містика, «духовний досвід», поняття, явище, визначення. Kompaniyets L.V. MYSTICS AND SPIRITUAL EXPERIENCE OR IN THE SPACE OF ELUSIVE LIMITS The relevance of mystics is substantiated in the article. It is emphasized that in the modern world a sustained interest to mysticism from everyday and religious consciousness, different spheres of society, is observed. The relevance of the topic is evident in light of everyday realities of modern mass culture, confirmed with the increasing attention to the phenomena of this kind within scientific communities. As the history of the mankind evolution proves, mystics has become popular and expanded its geographic distribution in transition and crisis. The semantic field of the term "mystics" is investigated, as well as the specifics of its relation to the "spiritual experience". The comprehension of the problem of demarcation between the specified terms is conducted. The flexibility of boundaries is defined, the flow of meanings from one concept to another is fixed. Mystics is presented as the foundation on which the whole space of human belief in a supernatural world is built, the dominant form of its incarnation on the plane of matter appears to be "spiritual experience", which is defined by us as an attribute of mystics, and hence of any religious, mystical tradition and culture. Mystical experience reveals itself as its source and ground. Proceeding from the kaleidoscope of scattered interpretations of the term "mystics" we offer the perspective of its consideration. As a result, the author’s definition of the term "mystics" is suggested. By mystics we understand the multifaceted cultural phenomenon associated with mystery, ideal worlds, having multiple forms of its incarnation and manifestation on the plane of matter, the source and mode of existence of which stands the "mystical experience". Mystics is also presented as a universal complex cultural phenomenon. Keywords: mystics, spiritual experience, elusive boundaries, a supernatural world.